Quantificação de machos e fêmeas de Heterodera glycines (Ichinohe, 1952) em cultivares de soja resistentes e suscetíveis - ARAÚJO, Fernando Godinho de (2009)
Soybean cyst nematode, Heterodera glycines Ichinohe, is one of the major phytopathological problems affecting the soybean, in the major producing countries of this legume. Eradication of H. glycines from contaminated areas is practically impossible. Thus, the soybean growers have to adapt control measures in order to maintain low population levels. The main control measures are crop rotation, soil management and use of resistant cultivars. With the purpose to evaluate the development of H. glycines and male/female ratio on soybean resistant and susceptible cultivars two trials were conducted during the years 2007 and 2008. Susceptible cultivars BRS Aracu, BRSGO Jatai, BRSGO Luziania, BRS Favorita RR, BRS Valiosa RR, BRS Silvania RR and resistant cultivars BRSGO Ipameri e BRSGO Chapadoes were evaluated. Soybean seedlings were transplanted to pots containing naturally infested soil with H. glycines, race 14, and, 10 days later, part of the plants remained in the pots to evaluate the females, while the other part was removed for hydroponic growth to evaluate the males. In the trial of 2008 the plants were divided in three lots, with the last one having the roots stained to count the juveniles and to evaluate survival rate. Resistant cultivars always maintained a small number of females and males, except for cultivar BRSGO Ipameri that had high countings of males. Only cultivars BRS Favorita RR and BRS Silvania RR had the expected sex ratio 1:1. All other susceptible cultivars had greater number of males than females, with ratios varying from 5:1 to 11:1. Survival rate was nil for both resistant cultivars, and varied from 6.75% to 35.00% for the susceptible cultivars. Regarding the number of cysts in 100 cc of soil the only cultivar that differed significantly from the others was the BRSGO Jatai on experiment conducted in 2007. The number of eggs per cyst varied, in both experiments, and the resistance did not influence the averages found